2009
DOI: 10.1111/j.1365-2591.2008.01538.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of periapical bone defects in human jaws using cone beam computed tomography and intraoral radiography

Abstract: With intraoral radiography, external factors (i.e. anatomical noise and poor irradiation geometry), which are not in the clinician's control, hinder the detection of periapical lesions. CBCT removes these external factors. In addition, it allows the clinician to select the most relevant views of the area of interest resulting in improved detection of the presence and absence of artificial periapical lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
222
1
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(245 citation statements)
references
References 41 publications
7
222
1
15
Order By: Relevance
“…A system was used with scores identified using numbers from 0 to 5, the CBCT-PAI index, and when the tomographic images of the AP were analyzed, the predominant score was in the range 0 to 0.50 mm, in both jaws, and 55.12% of endodontically treated lower teeth and 50% upper teeth showed no recurrence of lesion nor lesions in the process of repair. Lesions identified with scores between 0 and 1 corresponded to 83.47% of lesions in the mandibular and 78.89% in the maxilla, confirming the indication of CBCT for identifying AP of small dimensions [2][3] .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A system was used with scores identified using numbers from 0 to 5, the CBCT-PAI index, and when the tomographic images of the AP were analyzed, the predominant score was in the range 0 to 0.50 mm, in both jaws, and 55.12% of endodontically treated lower teeth and 50% upper teeth showed no recurrence of lesion nor lesions in the process of repair. Lesions identified with scores between 0 and 1 corresponded to 83.47% of lesions in the mandibular and 78.89% in the maxilla, confirming the indication of CBCT for identifying AP of small dimensions [2][3] .…”
Section: Discussionsupporting
confidence: 58%
“…According to several studies, the probability of apical periodontitis existing and not being identified by periapical or panoramic radiography, is considerable [2][3][4] . On the other hand, cone beam computed tomography (CBCT) images are high resolution 1,3,5 , permitting a more precise identification of the apical periodontitis (AP), providing more effective information about the size and location, since the superimposition of the neighboring anatomical structures [1][2][3][4][6][7][8][9][10][11][12][13][14][15] is eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…Penyerapan akar gigi insisor dalam kajian ini adalah lebih tinggi daripada yang dilaporkan oleh Lupi et al (1996) iaitu mencapai 80% selepas enam bulan rawatan ortodontik (Rajah 2). Penyerapan akar yang lebih tinggi dalam kajian ini mungkin disebabkan oleh penggunaan CBCT yang lebih sensitif daripada radiografi intra oral seperti yang telah dilakukan oleh Lupi et al (1996) dalam mengesan penyerapan akar gigi (Patel et al 2009). CBCT juga didapati lebih tepat daripada kaedah radiografi panoramik (Dudic et al 2009;Topkara et al 2012) dan radiografi periapeks (Sameshima & Sinclair 2001).…”
Section: Perbincanganunclassified
“…The sensitivity of periapical and panoramic radiography for the detection of apical periodontitis is 0.55 and 0.28 respectively, whereas CBCT can be considered as a gold standard with a sensitivity of 1 [35]. Patel, et al [36] reported with artificially created periapical lesions in human mandibles that 100% of the lesions were detected with CBCT.…”
Section: Endodonticsmentioning
confidence: 99%